MPARATIVE REPRODUCTIVE PERFORMANCE OF CAPTIVEREARED INDIAN STOCKS OF FENNEROPENAEUS MERGUIENSIS (DE MAN) WITH WILD-CAUGHT BROODSTOCK - WAIKHOM, GUSHEINZED; PILLAI, S. M. (Journal of the Inland Fisheries Society of India, 2021)
The potential for domestication of Fenneropenaeus merguiensis through closed life-cycle production and reproductive performance of the pond reared domesticated first generation broodstock were compared with wildcaught broodstock over a period of 8 weeks reproductive performance trial. There was significant variation (P